Optimalisasi Geostrategi Indonesia di Selat Malaka - Haqiqi, Frisky Amirul (Department of International Relations, Brawijaya University, 2020)
The Strait of Malacca is the busiest in the world. It happens because the Malacca Strait is one of the essential keys in energy trading. It started from being the target of pirates and armed robbery to the target of foreign intervention in the Malacca Strait. Feeling that its sovereignty was threatened, Indonesia did several things to maintain the sovereignty of the Malacca Strait as part of Indonesian territory. It was starting from the refusal to cooperate with foreigners to cooperate with the littoral state. This paper will explain the importance of the Malacca Straits in world trade and why Indonesia's sovereignty is threatened due to foreign activities in the Malacca Strait. This paper is based on Indonesia's geostrategy and National Resilience which is part of Indonesia's geostrategy itself.